When Things Fall Apart : Qualitative Studies of Poverty in the Former Soviet Union - Dudwick, Nora; Gomart, Elizabeth; Marc, Alexandre; Kuehnast, Kathleen (Washington, DC: World Bank, 2013)
This book documents the experiences of men, women, and children in Armenia, Georgia, the Kyrgyz Republic, Latvia, Moldova, Tajikistan, Ukraine, and Uzbekistan as they struggle with the dramatic changes in lifestyle and extreme poverty that followed the collapse of the Soviet Union. Based on hundreds of open-ended interviews conducted by local people over a span of five years, this book captures the particularities of poverty in each nation-state as well as a collective sense of disillusionment and a strikingly similar array of response to the crisis. certain aspects of the dynamics of poverty in the former Soviet Union and its interaction with gender, age, and ethnicity are highlighted. They deepen the understanding of how poor people in these countries experience, explain, and cope with their new circumstances. The studies also identify the range of cultural and administrative barriers that hinder poor people from accessing public services and exploiting economic opportunities. Above all, they highlight important psychological dimensions of poverty in the FSU, including the collapse of values and beliefs that accompanied the increase in poverty and the resulting disorientation experienced by the poor. Finally, the studies demonstrate the continuing importance of informal support networks and the persistence of paternalistic relationships and expectations that the old regime had fostered.